Association between vaccine dose and risk of hepatitis B virus infection in Fujian Province, China - Jiang-Nan Wu; Li-Fang Huang; Zhi-Qiang Lin; Yong Zhou (Taylor & Francis Group, 2022)
The increased dose of hepatitis B vaccine has been adopted for newborns since 2013 in Fujian, China. However, little is known about the impact of this measure on hepatitis B virus (HBV) prevention. We used the seroepidemiological surveys conducted in 2014 and 2020 to address the concern. Compared with subjects who received a 5 μg hepatitis B vaccine, participants who took a 10 μg hepatitis B vaccine were associated with a lower risk of HBV infection (adjusted odds ratio [OR] 0.26, 95% confidence interval [CI]: 0.10-0.68) and a marginal reduction risk of anti-HBc positive (OR, 0.37; 95% CI: 0.13-1.08; P = .07), but not for HBsAg carrier risk. The relation between vaccine dose and risk of anti-HBc positive (OR, 0.20; 95% CI: 0.05-0.81) became slightly stronger and significant among children investigated in 2020 who probably received universal vaccination. No significant association was found for subjects whose mothers were positive for HBsAg. The current 10 μg hepatitis B vaccines for universal vaccination for newborns are reasonable and effective in HBV prevention. More measures should be taken to reduce the risk of HBsAg carriers for infants whose mothers are positive for HBsAg.